What is Islamic Political Economy? A Review - Ahmad (Ekonomi Islam Indonesia, 2021)
One of the factors that affect the economic performance of a country is the political economy system used. The existing political economy systems such as capitalism and socialism are considered unsuccessful in creating economic development and social welfare. Unlike other religions, Islam has its views in almost all areas of individual and community life, Islamic views are built on the texts of the Qur'an and As-Sunnah. This study aims to determine the development of Islamic Political Economy research trends published by leading journals on Islamic economics. The data analyzed consisted of 584 indexed research publications. The data is then processed and analyzed using the VoS viewer application to find out a bibliometric map of the development of Islamic Political Economy research.